Investigating the Structure and Content Analysis of “Kelileh and Demneh Textbooks” Description of Hussein Haddad - Mehran Najafi Hajivar; Sajad Najafi Behzadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Ancient texts such as “Kelileh and Demneh” have a great place and importance among students due to their content and educational concepts. The linguistic structure (technical prose) and the stylistic feature of “Kelileh and Demneh” are such that most audiences have difficulty communicating with this work. The purpose of the present study is to review the book “Kelileh and Demneh” Sharh Hossein Haddad by Qadyani Publications. This book, which has been described and compiled based on the correction of Minavi and Hassanzadeh Amoli, in addition to its advantages and positive components, is not without its drawbacks. In this research, by using the method of content analysis and collecting information in the form of library documents, while criticizing and reviewing the book “Kelileh and Demneh” Sharh by Hossein Haddad, a comparison with other versions of Kelileh has been carried out, and the book has been reviewed from two perspectives: form and content. The results of the research showed that there are problems and content objections (in the field of vocabulary, Arabicization, allusions, etc.) in the above-mentioned description that should be considered in the new edition. The lack of attention of the commentator to the Arabic text of “Kelileh and Demneh”, contenting himself only with the old versions of the work, not referring to important sources in the field of Arabic and Persian dictionaries, dictionary of allusions, etc. caused such problems in the book.